Optimised PLC transmission over pulse‐width modulated network. Issue 12 (6th November 2019) - Descamps, Anne‐Sophie; Zaraneh, Nabil; Batard, Christophe; Ginot, Nicolas
Abstract : In industrial application of adjustable speed drive for electrical motors, some sensors are supplying mandatory information such as speed or position of the rotor to the electronic command. In most deployed applications, these data are transmitted through an additional dedicated line. In order to avoid this additional installation, power line communication (PLC) technology can be used. This study proposes a PLC communication solution between an inverter and a motor through a variable length cable. This solution relies on the modelling of this communication channel as well as the characterisation of the pulse‐width modulated signal. The communication parameters such as carrier frequency or modulation format (quadrature phase shift keying etc.) have been optimised to reduce the channel‐to‐noise ratio in this context. An error free 2 Mbit/s communication has been achieved on a 2 kW test bench.